KARAKTERISASI STOMATA DAUN PEGAGAN (Centella asiatica (L.) Urban.) PADA KETINGGIAN WILAYAH BERBEDA DI PULAU AMBON - Hermalina Sinay; Max H Lesilolo (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2020)
The purpose of this study was to determine the anatomical structure of pegagan leaves through stomata characterization at several different locations on Ambon Island. Survey method was used in this research. The sample was taken in nine villages were spread from lowlands to the highlands on Ambon Island. The procedure of semi-permanent preparations was done by whole mount method. Stomata characterization was done towards the stomata number, stomata density, and stomata index. The collected data were analyzed by descriptive analysis and performed in the form of table or figure. the research result shows that leaf with high stomata number was tend to high in stomata density and stomata index. Based on this research result, it could be conclude that there are no difference of stomatal structure of Pegagan leaves in all location were sample collected. The difference has shown by numbers, density, and stomatal index. The highest Numbers, density and stomatal index shown on Pegagan leaves in lowland, and the lowest that shown in this research on Pegagan leaves in highland